What keeps healthcare professionals from advising their patients who smoke to quit? A large-scale cross-sectional study - Eline Meijer; Rianne Van der Kleij; Niels Chavannes (Tobacco Induced Diseases, 2018)
Background Quit-advice provided by healthcare professionals effectively increases quit rates. Tobacco dependence treatment guidelines therefore recommend providing quit-advice to all patients who smoke (PWS), however, many healthcare professionals do not advise PWS to quit. This results in worse patient outcomes and higher healthcare costs. We examined determinants of providing quit-advice among a large sample of healthcare professionals from different fields, most of which have not been included in research on tobacco discouragement before.